Gambaran Karakteristik Pasien Kanker Payudara Yang Menjalani Kemoterapi - Utami, Desti Kurnia; Malini, Hema; Sarfika, Rika (Universitas Fort De Kock Bukittinggi, 2022)
Background: The development of breast cancer cases, currently worldwide has become a major health problem among non-communicable diseases. In the healing process, chemotherapy is the main choice in the treatment of breast cancer. This study aims to describe the characteristics of breast cancer undergoing chemotherapy at two hospitals in the city of Padang. Methods: This type of research is cross sectional with a descriptive approach. Results: The results of the study showed the characteristics of breast cancer patients undergoing chemotherapy with an age range of 46-55 years, low education level, stage II cancer and second cycle of chemotherapy. Conclusion: Breast cancer patients undergoing chemotherapy at two government hospitals in Padang City are mostly elderly, low grade, stage 2 cancer, and 2nd home cycle. Suggestion: it is expected that health workers will provide education and counseling about early detection of breast cancer to reduce patients who come to the hospital with an advanced stage.Keywords: Breast Cancer, Chemotherapy, Breast Cancer Stage